Basic Analysis For Taking Learning Policies In The Pandemic Time Covid 19 - Rahmat Hidayat; Eko Risdianto; Titin Aprilatutini; Nova Yustisia (Universitas Bengkulu, 2021)
This research aims to conduct a basic analysis of policies on learning services during the Covid-19 period towards practice subjects at IAIN Curup Bengkulu Indonesia. This type of research is Research & Development (R&D) by ADDIE at the need assessment stage. Case studies are carried out in the Physical Education course at the Curup state Islamic Institute Bengkulu Indonesia. The population in this study were students of IAIN Curup who took Physical Education courses. The research sample was 238 students. The sampling technique used was the purposive sampling technique and the instrument used was a closed questionnaire. Data were analyzed by using quantitative and qualitative analysis. From this research, it will be obtained the results of an analysis of policies on learning services during the Covid-19 period towards practicing subjects at IAIN Curup. Through this research, it is concluded that most of the policies regarding learning services carried out during the pandemic are still not very good.